Factors associated with past year physical and sexual intimate partner violence against women in Zimbabwe: results from a national cluster-based cross-sectional survey - Simukai Shamu; Patience Shamu; Mercilene Machisa (Taylor & Francis Group, 2018)
Background: Intimate partner violence (IPV) against women continues to be a public health burden globally. Objectives: To assess prevalence and factors associated with women's experiences of past 12 months physical/sexual IPV Methods: A two-stage cluster-based national cross-sectional survey in which women were randomly selected for participation was conducted among 5295 women aged 15-49 years. IPV in the last 12 months was assessed using the WHO interviewer-administered questionnaire for measuring violence against women. Participants' wife beating attitudes, partner controlling behaviours, household decision-making, STI history, HIV status and demographic characteristics were assessed. Multivariate logistic regression was conducted to assess factors associated with IPV. Results: Of the 5292 women interviewed, mean age was 31.5 years and 84.7% were married. Over one-fifth of the women (20.2: 95%CI 19.1-21.3) were physically/sexually abused in the last 12 months. IPV was associated with gender inequitable norms and practices which include lacking household decision-making power (aOR 2.05, 1.71-2.47), experiencing low (aOR 2.05; 1.71-2.47) or high (aOR 4.5; 3.62-5.60) partner controlling behaviours (vs none) and endorsing low (aOR 1.29) or high (aOR 1.36) wife beating attitudes (vs none), having sexual self-efficacy (aOR 1.19; 1.10-1.41), experiencing emotional abuse (aOR 4.50; 3.62-5.60) and having a sexually transmitted infection (STI) (aOR 1.36, 1.04-1.77). IPV was also associated with women's empowerment factors including possessing household assets (aOR 1.26, 1.03-1.54) and reporting current media usage (aOR 1.29; 1.04-1.61). Demographic factors associated with IPV were age and number of children. Conclusions: This study provides evidence that IPV is a significant public health and societal problem as one in five women were abused in the past year. Younger women, less empowered women, women in inequitable intimate relationships and women endorsing traditional gender norms were at increased risk of abuse. IPV prevention programmes must prioritise transforming traditional gender norms and women's economic empowerment.